1993
DOI: 10.1159/000282469
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Immunotherapy (IL2 + LAK + Inhibition of Prostaglandin Synthesis) on Peripheral Blood Immune Parameters and in vitro Cytokine Production in Metastatic Renal Cell Carcinoma

Abstract: Previous results on the peripheral blood immune status of renal cell carcinoma had indicated immunosuppression in metastatic disease, possibly mediated by prostaglandin E2 (PGE2). In the present study the immunologic effects of inhibition of PG synthesis by piroxicam in combination with interleukin 2 (IL 2) + lymphokine-activated killer (LAK) cell therapy were tested by immunomonitoring. In additon to peripheral blood parameters (lymphocyte subpopulations, neopterin, β2-microgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…64,65 Favorable responses to current immunotherapy have been observed in patients in whom therapy resulted in decreased PG levels, while conversely those with tumor progression and resistance to therapy have had persistently elevated PG. 66,67 It has also been shown that inhibitors of PG biosynthesis may enhance the therapeutic response. Because of this putative role of PGs in renal cell carcinoma progression and treatment response, and because PGs are directly derived from the COX-2 catalyzed metabolism of arachidonic acid, COX-2 inhibitors may potentially function to decrease PG levels and may have antineoplastic effects in renal tumors.…”
Section: Renal Cancermentioning
confidence: 99%
“…64,65 Favorable responses to current immunotherapy have been observed in patients in whom therapy resulted in decreased PG levels, while conversely those with tumor progression and resistance to therapy have had persistently elevated PG. 66,67 It has also been shown that inhibitors of PG biosynthesis may enhance the therapeutic response. Because of this putative role of PGs in renal cell carcinoma progression and treatment response, and because PGs are directly derived from the COX-2 catalyzed metabolism of arachidonic acid, COX-2 inhibitors may potentially function to decrease PG levels and may have antineoplastic effects in renal tumors.…”
Section: Renal Cancermentioning
confidence: 99%